Analisis Komparasi Kinerja Keuangan Perusahaan Tekstil Yang Terdaftar di Bursa Efek Indonesia Sebelum dan Sesudah Pengumuman Masyarakat Ekonomi ASEAN - Tida, Neroldi (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
This research aims to know the differences in financial performance of the textile companies that registered in the Indonesia Stock Exchange (ISE) before and after the announcement of the ASEAN Economy Community (AEC). The test results in this research indicate that there is no differences financial performance that significant of the textile companies that registered in the Indonesia Stock Exchange (ISE)Â  period before and after the announcement of the ASEAN Economic Community (AEC)Keywords: Financial Performance, Current Ratio, Quick Ratio, Debt to Assets Ratio,Debt to Equity Ratio, Return On Equity, Net Profit Margin, Total Assets Turnover, Earnings per Share and Sales Growth